1994
DOI: 10.1143/jjap.33.4442
|View full text |Cite
|
Sign up to set email alerts
|

Selective Etching of Hydrogenated Amorphous Silicon by Hydrogen Plasma

Abstract: The selective etching of hydrogenated amorphous silicon (a-Si:H) with respect to crystalline Si (c-Si) by hydrogen plasma is investigated. We have revealed that a-Si:H is etched ten times faster than c-Si. With lower etching temperature, etching selectivity and etching rate of a-Si:H and c-Si increase. Under the high-pressure condition, the etch rate becomes low because the bright region of a very-high-frequency plasma moves away from the grounded electrode. The etching rate of a-Si:H is not sensitiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
18
1

Year Published

2001
2001
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(21 citation statements)
references
References 20 publications
2
18
1
Order By: Relevance
“…Otobe et al 45 found that the roughness of H etched Si increased with increasing substrate temperature, consistent with our results. Other possible explanations for the role of hydrogen have been put forth by a number of authors: Nakata et al suggest that the atomic hydrogen coverage or the growing surface enables surface species to have a higher mobility, 46 explaining the decrease in roughness with decreasing substrate temperature.…”
Section: Discussionsupporting
confidence: 93%
“…Otobe et al 45 found that the roughness of H etched Si increased with increasing substrate temperature, consistent with our results. Other possible explanations for the role of hydrogen have been put forth by a number of authors: Nakata et al suggest that the atomic hydrogen coverage or the growing surface enables surface species to have a higher mobility, 46 explaining the decrease in roughness with decreasing substrate temperature.…”
Section: Discussionsupporting
confidence: 93%
“…12 However, Wanka and Schubert 13 observed that the aSi:H etch rate by atomic H, formed with a hot-tungsten filament, reduces for temperatures above room temperature. Two mechanisms can explain this observation: reduced atomic H surface coverage at elevated temperatures due to either enhanced atomic H recombination and desorption 14 or enhanced atomic H diffusion into the bulk. 7 The chemical a)…”
Section: Introductionmentioning
confidence: 99%
“…6,[9][10][11][12][13] Preferential insertion of atomic hydrogen in strained Si-Si bonds and subsequent silicon etching lead to a higher etch rate of amorphous silicon ͑a-Si: H͒ relative to crystalline Si. [14][15][16] In a recent Letter, 17 we demonstrated that this difference in etch rate can be exploited to determine in situ the phase composition of silicon films in the c-Si: H growth regime. In this letter we introduce a quantification of the etch product density in terms of the absolute atomic hydrogen flux.…”
mentioning
confidence: 95%